PERAN KEPALA DESA DALAM PEMBANGUNAN DESA DI KECAMATAN MEKARSARI KABUPATEN BARITO KUALA - Bakhtiar Bakhtiar; Rizalul Gadi (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
The results of the study show that 1) The role of the Village Head in the developmentof the Village in Mekarsari Subdistrict as a policeman, innovator and stabilizer bycarrying out various plans, proposals and actions in achieving a better villagedevelopment goal. 2) Obstacles of the Village Head in carrying out village developmentin Mekarsar District, Barito Regency, among others: a) The still low quality of HumanResources or education of officials and the community who carry out the Villagedevelopment process in Mekarsari District. b) Limited budget for village developmentin Mekarsari District. c) Low allowances for the Village Head so that the level ofwelfare of the village head is very low. d) Lack of supervision and guidance to theVillage Head from the Regional Government. 3) Solution of the Village Head inimplementing Village development in Mekarsar District, Barito Kuala Regency, amongothers: a) Improving the quality of Human Resources and education of officials and thecommunity who carry out the Village development process in Mekarsari District. b)Propose additional budgets for village development in Mekarsari District. c) Increasingbenefits for the Village Head so that the level of welfare of the village head becomesbetter. d) Improve supervision and guidance to the Village Head from the RegionalGovernment, so that the implementation of development runs smoothly.